Influence of the deposition process and substrate on microstructure, phase composition, and residual stress state on as-deposited Cr-Al-C coatings. (January 2023) - Heinze, Stefan; Krülle, Tim; Ewenz, Lars; Krywka, Christina; Davydok, Anton; Stark, Andreas; Cremer, Rainer; Leyens, Christoph
Graphical abstract: Highlights: The thin films consist of amorphous and metastable (Cr, Al)2 C, with the ratio dependent on the coating process and substrate. Residual stress analysis was performed with in situ and ex-situ synchrotron X-ray diffraction. Amorphous volumes, with a higher connection area to the substrate, mainly buffer the residual stress from the deposition. Compressive residual stress reduces tensile stress caused by cooling, but is not stable during post-heat treatment at 700 °C. Abstract: This paper focuses on the influence of the High Power Pulsed Magnetron Sputtering (HPPMS) and Direct Current Magnetron Sputtering (DCMS) coating deposition processes, the bias voltage, deposition temperature, and substrate on various properties of the as-deposited state of Cr-Al-C thin films. Three substrates with different coefficients of thermal expansion and electrical conductivity were used. To investigate the microstructure, phase composition, residual stress state, and mechanical properties, ex-situ and in situ synchrotron experiments were conducted accompanied by electron microscopy and nanoindentation. As-deposited Cr-Al-C coatings consisted of amorphous and crystalline areas, with the ratio highly dependent on the deposition process and substrate. The crystalline phase was identified as metastable (Cr, Al)2 C. The highest crystallinity was determined for DCMS coatings. Increasing temperature and decreasing bias voltage increased coating crystallinity for HPPMS coatings. The influence of the deposition process and bias voltage was highly reduced for the substrate with low electrical conductivity. In-situ investigations of the stress state of amorphous areas revealed, that those were acting as a residual stress buffer. The hardness and Young's modulus of the coatings were found to increase with crystallinity and were slightly increased for crystalline HPPMS coatings compared to DCMS coatings.